(untitled) (Research, Society and Development, 2020)
Alzheimer’s is a disease that occurs in the connections of brain cells, which degenerate and die, thus causing the gradual destruction of memories and memory. This study sought to report an experience about the implementation of a program of activities and exercises developed to promote health promotion and an effective coping with Alzheimer’s disease with elderly people from a long-term institution. This is a descriptive study, of the experience report type, based on the problematization methodology of the Arco de Maguerez. Among the main results obtained, it was found that the action brought many benefits to the participants, since it directly assisted in the promotion of well-being, as well as attenuating the degenerative process of the disease’s dementia. In addition, it is concluded that the activities that were developed favored the consolidation of the aspects that constitute comprehensive care, covering various needs of the user and assisting him in coping with the pathology.